THE ROLE OF PESANTREN IN THE DEVELOPMENT OF SHARIA ECONOMY IN INDONESIA - Faisal Affandi; Melda Diana Nasution (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2023)
Pesantren as one of the oldest educational institutions in Indonesia has an important role in the process of developing Islamic economics in Indonesia. Islamic boarding schools, with their various strategic potentials, deserve to be the locomotive of the Islamic economy. The purpose of this study is to analyse how the role of Islamic boarding schools in the development of Islamic economics in Indonesia. This research is a library research whose data is through library sources and other references related to the role of Islamic boarding schools in efforts to develop Islamic economics in Indonesia. The results showed that, (1) Pesantren is one of the oldest educational institutions that plays an important role as a locomotive of Islamic economics in Indonesia because it was born on the initiative and initiative of Muslim community leaders who are inherent and become an inseparable part of the social system of Indonesian Muslim society, (2) Pesantren can be a pioneer of the people's economy because the commitment of the students in their religion can affect the economic activities carried out by the students and the focus of pesantren activities on Islamic studies can make it a driver of Islamic economics in the community as well as giving birth to young entrepreneurs with Islamic souls, (3) There are three approaches that can be taken to develop pesantren as a centre for the development of Islamic economics and community economics, namely the teaching reform approach, the approach taken by the government and the approach originating from the initiative of private organisations that develop science, (4) Optimisation of all resources owned by pesantren can create a great force in the economy if managed properly.